2018
DOI: 10.1108/ijoes-05-2017-0071
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stakeholder pressure and corporate governance on the sustainability report quality

Abstract: Purpose -The purpose of this study is to examine the effects of stakeholder pressure and corporate governance on the quality of sustainability report. This study uses environment, employee, consumer and shareholder as stakeholders, while board of commissioner effectiveness and family ownership are used as corporate governance components.Design/methodology/approach -This research uses multiple regression method with total observations of 123 sustainability reports of listed firms on Indonesia Stock Exchange in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
1
92

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(205 citation statements)
references
References 74 publications
7
105
1
92
Order By: Relevance
“…It is in line with the opinion of Khafid et al (2018) that companies with good governance practices can disclose information about disclosure of responsibility for company activities, particularly regarding sustainability reports. The board of commissioners as one of the corporate governance structures is tasked with overseeing management in order to act is fit with the interests of stakeholders (Rudyanto & Siregar, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is in line with the opinion of Khafid et al (2018) that companies with good governance practices can disclose information about disclosure of responsibility for company activities, particularly regarding sustainability reports. The board of commissioners as one of the corporate governance structures is tasked with overseeing management in order to act is fit with the interests of stakeholders (Rudyanto & Siregar, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Environmental damage reflects the company's low responsibility to the environment. The research conducted by Rudyanto & Siregar (2018) [3]which examined 123 sustainability reports on companies listed on the Indonesia Stock Exchange in 2010-2014 found that the quality of sustainability reports in Indonesia was still low. It is indicated by the low number of opinions on sustainability reports and independent party assessments regarding the GRI Application Check.…”
Section: Introductionmentioning
confidence: 99%
“…Variabel slack resources diukur dengan logaritma natural dari kas dan setara kas (Arora dan Dharwadkar, 2011). Variabel family ownership diukur berdasarkan persentase kepemilikan saham keluarga baik secara individu atau kepemilikan melalui perusahaan (Rudyanto dan Siregar, 2018). Penelitian ini juga menggunakan variabel kontrol seperti age, size (total asset), dan leverage (DER).…”
Section: Metodeunclassified
“…An abundant research on the CSR disclosure by companies has been extensively conducted embracing different theoretical perspectives. Rudyanto and Siregar (2018) have focused on the ethical side inherent in sustainability to examine the pressure of stakeholders on CSR quality. They mentioned that many ethical theories used by some authors (e.g.…”
Section: Research Background: the Csr Disclosure And Stakeholders Thementioning
confidence: 99%
“…Therefore, it is important to know whether the influence of the stakeholders will improve the quality of information in the sustainability report as well as the quantity. Rudyanto and Siregar (2018) examined the effects of stakeholder pressure and corporate governance on the quality of sustainability report as it was vital to win the negotiation process with stakeholders.…”
Section: Introduce the Problemmentioning
confidence: 99%